PENGARUH STATUS SOSIAL TERHADAP IBADAH SISWA DI SEKOLAH MENENGAH PERTAMAISLAM KEPENUHAN KABUPATEN ROKAN HULU - Leniwati Leniwati; Dila Roza (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This study aims to determine the effect of social status in Islamic Junior High School in Rokan Hulu Regency. This type of research is quantitative with the correlation method. The population in this study were all students of the Islamic Junior High School Kepanjangan Rokan Hulu Regency with a total of 230 students. While the research sample uses the Proportional Random Sampling method, so that the sampling uses 10%, the number of research samples is 70 students. Data collection techniques using questionnaires and documentation. The data analysis technique used SPSS calculation. The results of the study are that there is an influence of social status on student worship at the Islamic Junior High School of Rokan Hulu Regency, the correlation results show that r count is greater than r table (0.523> 0.244), it is stated that the alternative hypothesis (Ha) is accepted and the hypothesis is nil (H0 ) rejected.While the contribution of social status to student worship is only 27.3%, the remaining 72.7% is influenced by other variables not discussed in this study